Advances and perspectives on perylenequinone biosynthesis - Deng, Huaxiang; Liang, Xinxin; Liu, Jinbin; Zheng, Xiaohui; Fan, Tai-Ping; Cai, Yujie (Frontiers in Microbiology, 2022)
Under illumination, the fungal secondary metabolites, perylenequinones (PQs) react with molecular oxygen to generate reactive oxygen species (ROS), which, in excess can damage cellular macromolecules and trigger apoptosis. Based on this property, PQs have been widely used as photosensitizers and applied in pharmaceuticals, which has stimulated research into the discovery of new PQs and elucidation of their biosynthetic pathways. Recent progress is reviewed in three sections: (1) the sources, structural diversity and biological activities of microbial PQs (2) elucidation of PQ biosynthetic pathways, associated genes and mechanisms of regulation (3) advances in pathway engineering and future potential to modify cellular metabolism and improve PQ production.